Pengaruh Pemanfaatan Powerpoint Dalam Pembelajaran Terhadap Prestasi Belajar Matematika Tingkat Sekolah Dasar Ditinjau Dari Gaya Belajar Siswa - Darmadi Darmadi (Jurnal Pendidikan, 2009)
The aims of this research are: 1) to identity the significance of PowerPoint presentation utilization on the mathematics achievement of the students of elementary school, 2) to depict the significance of the students’ learning styles on mathematics achievement of the students of elementary school, and 3) to identity the presence of interaction between the students’ learning styles and the utilization of PowerPoint presentation on the mathematics achievement of the students of elementary school. Pilot instructional design is the PowerPoint – utilizing one, while the control design is the conventional one. Learning styles includes: visual, auditorial and kinesthetic learning styles. The population of this research is students of elementary schools in Madiun Municipality. The results of the research are: 1) the PowerPoint utilization in math class can significantly increase the students’ achievement, 2) the students’ learning styles significantly influence the students’ achievement. The visual learning styles are stronger than auditorial and kinesthetic which similar, and 3) there is interaction between conventional and attested students’ learning styles. Under conventional learning strategy, students’ learning styles do not influence the student achievement. Under the pilot learning strategy by utilizing PowerPoint presentation, the students’ learning styles influence the students’ achievement. Kinesthetic and auidtorial learning styles similarly influence the students’ achievement, but visual learning style results in a better students’ achievement. The utilization of the PowerPoint presentation program does not significantly influence the achievement of the students with visual and kinesthetic learning styles, but it significantly influences the achievement of the students with auditorial learning style.